2000
DOI: 10.1021/ma992053a
|View full text |Cite
|
Sign up to set email alerts
|

Seeded Semibatch Emulsion Polymerization ofn-Butyl Acrylate. Kinetics and Structural Properties

Abstract: The seeded semibatch emulsion polymerization of n-butyl acrylate was investigated using potassium persulfate as initiator at 75 °C. The effect of initiator concentration and monomer feeding time (feed flow rate) on the kinetics, fraction of gel, molecular weight distributions, and level of branches were studied. It was found that the amount of gel formed was independent of initiator concentration and monomer feed flow rate if the process proceeded under starved conditions. On the other hand, the higher the ini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
242
0
5

Year Published

2001
2001
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 170 publications
(261 citation statements)
references
References 29 publications
14
242
0
5
Order By: Relevance
“…2 Because most of the branches are formed by backbiting, in the homopolymerization of acrylate monomers the formation of branches can be described by Scheme 1. The propagating secondary radical, R 2 * , undergoes intramolecular chain transfer to polymer via a six membered ring transition state and subsequent propagation from the formed tertiary radical, R 3 Branching fraction= …”
Section: 18mentioning
confidence: 99%
See 1 more Smart Citation
“…2 Because most of the branches are formed by backbiting, in the homopolymerization of acrylate monomers the formation of branches can be described by Scheme 1. The propagating secondary radical, R 2 * , undergoes intramolecular chain transfer to polymer via a six membered ring transition state and subsequent propagation from the formed tertiary radical, R 3 Branching fraction= …”
Section: 18mentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12] Transfer to polymer in acrylic monomers has been shown to be mainly due to intramolecular transfer via a six membered ring transition state, resulting in a mid chain radical. [13][14][15][16][17] In general, for most polymerizations which are conducted at a temperature of <100°C , the most likely fate of the midchain radical is propagation, leading to the formation of quaternary carbons that are a fingerprint of this process and can be detected by 13 C NMR.…”
Section: Introductionmentioning
confidence: 99%
“…As long as the reaction rate of short-chain branching is much smaller than the propagation reaction, which is usually the case for FRPs, the effect of backbiting on the formed MWD, as well as the radius of gyration, would not be significant. Although it has been reported that the frequency of short-chain branching is greater than that of long-chain branching, especially for acrylic monomers [2,3], the backbiting reaction is neglected in the present theoretical investigation in which the effects of polymerization process on the MWD and the 3D size distribution are highlighted.…”
Section: Introductionmentioning
confidence: 97%
“…[24][25][26] Although, not unlike the discussion about the monomer reaction order x, other factors such as transfer to monomer were discussed, 24 Asua and coworkers soon made the connection to the transfer to polymer reactions. [27][28][29][30][31][32] No reliable k p data for conditions under which polymerizations usually are applied are available, 33 and only rate coefficients that are extrapolated from the low-temperature polymerization data are in use. However, this extrapolation can only be seen as an approximation for the propagation rate coefficient of the SPR species, and the effective propagation rate is much lower due to the significantly reduced activity of the MCRs.…”
Section: Introductionmentioning
confidence: 99%